Policy-Induced Social Interactions and Schooling Decisions - Matteo Bobba; Jeremie Gignoux (Inter-American Development Bank (IDB), 2011)
This paper considers a conditional cash transfer program targeting poor households in small rural villages and studies the effects of the geographic proximity between villages on individual enrollment decisions. Exploiting variations in the treatment status across contiguous villages generated by the randomized evaluation design, the paper finds that the additional effect stemming from the density of neighboring recipients amounts to roughly one third of the direct effect of program receipt. Importantly, these spatial externalities are concentrated among children from beneficiary house- holds. This suggests that the intervention has enhanced educational aspirations by triggering social interactions among the targeted population.
Keywords: C9; I2; J2; O2; 330